The practices of conflict management styles from different perspectives - Siti Marziah Zakaria; Nor Hazila Mat Lazim (Penerbit Universiti Kebangsaan Malaysia, 2018)
Conflict is a form of competing struggle between two parties that possess different and incompatible goals, which commonly involve a win-lose situation. Thomas and Killman suggested that conflict management can be addressed in five styles, namely competing, collaborating, compromising, avoiding, and accommodating. These styles have been widely favored and practiced by different cultures and religious orientation. Apparently, the five conflict management styles proposed by Thomas and Killman in 1974 have been adopted in most cultures. Therefore, the aim of this concept paper is to provide a detailed discussion on the practices of different conflict management styles in various cultures and settings. Conflict management styles are inevitably related to culture, religion and orientation. It is also highly dependent on situational and environmental factors. Apparently, conflict management styles may function in phases. Thus, the phases should also be examined as conflict management styles may work in different phases for different types of setting.